Social and Religious Networks with Respect to the Health Behaviors of African American Women: A Systematic Review - Derboghossian, Grace (Journal of religion and health, 2025)
The aim of this systematic mixed studies review was to examine how social networks influence physical activity and dietary patterns among African American women. We searched PUBMED, CINAHL, JSTOR, SocioIndex, Medline, Cochrane Library, sportDISCUS, and PsycINFO to review articles published between Jan 1, 2007, and July 1, 2021. Only 23 studies met the inclusion criteria. All studies were conducted in the US. Social support received from family members, friends, and churches was found to positively influence physical activity and/or dietary patterns among African American women. An inconsistent relationship was found between social network size, health behavior characteristics of social networks, and physical activity and/or dietary patterns among African American women. Future research should incorporate structural and functional social network strategies to promote physical activity and healthy eating behaviors effectively and sustainably among African American women.